EFFECT OF ANTIHELMINTHIC THERAPY ON THE SKIN PROCESS IN ROSACEA PATIENTS IN COMBINATION WITH OPISTHORCHIASIS - M. L. Aripova (Бюллетень сибирской медицины, 2015)
The article presents results of examination of 144 patients, including 64 patients with rosacea in combination  with  chronic  opisthorchiasis  (group  1)  and  80  patients  with  rosacea  without  opistorchiasis (group 2). Rosacea patients with concomitant chronic opisthorchosis revealed more severe clinical variants. Mean values of the index scale diagnostic assessment of rosacea is significantly higher than in patients rosacea without helminthiasis, indicating a more severe course. Dissatisfaction with the quality of life in patients with rosacea in combination with chronic opisthorchiasis was significantly higher than in patients with rosaceaonly. Patients with rosacea in combination with chronic opisthorchiasis reveled prevalence of anxiety and depression in scale of HADS. There are also were a comparative analysis of the clinical picture in patients with rosacea anthelmintic therapy and without deworming.